Formation of single-dominant-species patches of Dicranopteris dichotoma primarily influenced by understory light intensity - Dong, Dubin; Tong, Jiali; Liao, Liang; Yi, Lita; Yan, Wende; Yu, Fei (Frontiers in Plant Science, 2024)
Dicranopteris is an ancient and widespread genus of ferns in pantropical regions, and its ecological function, including ecosystem recovery and succession control, has been confirmed and received increasing research attention. Relevant papers on this topic have already been published in Frontiers in Plant Science (Yang et al., 2021; Hu et al., 2023).However, the formation mechanism of the single-species dominant community of D. dichotoma in subtropical forests remains unclear. Therefore, we conducted a study across four different community types (grassland, coniferous forests, coniferous and broadleaved mixed forests, and evergreen broadleaved forests) to investigate the environmental factors that influence the formation of the dominant Dicranopteris community. These results will help to clarify the roles of Dicranopteris in microclimate maintenance and soil organic carbon and nutrient sequestration to promote the restoration process of degraded subtropical ecosystems.